PROFIL KECEMASAN PESERTA DIDIK DALAM MERENCANAKAN ARAH KARIR PADA KELAS X DI SMA NEGERI 4 PADANG - Visia, Dora - (Bimbingan dan Konseling, 2014)
This research focus on anxiety is experienced by student that related to planning career.The purpose of the research is to describe: 1) Profile of studentâs anxiety on planning career whichlooking from physical symptom. 2) Profile of studentâs anxiety on planning career that lookingfrom psychic symptom. Type of the research is quantitative descriptive research with population awhole student of SMA Negeri 4 Padang grade X in period 2014-2015 with number of student 252persons. The research use simple random sampling technique, amount of student is 72 persons.Instrument that used in this research is questionnaire and for analysis data using percentagetechnique. The result of this research revealed that in general profile of studentâs anxiety onplanning career is 54.17%, it means that the criteria is very high. The result of this research basedon sub variables is: 1) Profile of studentâs anxiety on planning career which looking from physicalsymptom is 45.83% at high criteria. 2) Profile of studentâs anxiety on planning career that lookingfrom psychic symptom is 61.11% at high criteria. Based on this research, researcher suggested thestudent to find more information about career. So in panning career student donât feel anxiety likenow.